Genetic regulatory networks for salt-alkali stress in Gossypium hirsutum with differing morphological characteristics - Yanchao Xu; Richard Odongo Magwanga; Xiu Yang; Dingsha Jin; Xiaoyan Cai; Yuqing Hou; Yangyang Wei; Zhongli Zhou; Kunbo Wang; Fang Liu (BMC Genomics, 2020)
Abstract Background Cotton grows in altering environments that are often unfavorable or stressful for its growth and development. Consequently, the plant must cope with abiotic stresses such as soil salinity, drought, and excessive temperatures. Alkali-salt stress response remains a cumbersome biological process and is regulated via a multifaceted transcriptional regulatory network in cotton. Results To discover the molecular mechanisms of alkali-salt stress response in cotton, a comprehensive transcriptome analysis was carried out after alkali-salt stress treatment in three accessions of Gossypium hirsutum with contrasting phenotype. Expression level analysis proved that alkali-salt stress response presented significant stage-specific and tissue-specific. GO enrichment analysis typically suggested that signal transduction process involved in salt-alkali stress response at SS3 and SS12 stages in leaf; carbohydrate metabolic process and oxidation-reduction process involved in SS48 stages in leaf; the oxidation-reduction process involved at all three phases in the root. The Co-expression analysis suggested a potential GhSOS3/GhCBL10-SOS2 network was involved in salt-alkali stress response. Furthermore, Salt-alkali sensitivity was increased in GhSOS3 and GhCBL10 Virus-induced Gene Silencing (VIGS) plants. Conclusion The findings may facilitate to elucidate the underlying mechanisms of alkali-salt stress response and provide an available resource to scrutinize the role of candidate genes and signaling pathway governing alkali-salt stress response.